Genome sequences of 65 Helicobacter pylori strains isolated from asymptomatic individuals and patients with gastric cancer, peptic ulcer disease, or gastritis. Issue 2 (23rd May 2013) - Blanchard, Thomas G.; Czinn, Steven J.; Correa, Pelayo; Nakazawa, Teruko; Keelan, Monika; Morningstar, Lindsay; Santana‐Cruz, Ivette; Maroo, Ankit; McCracken, Carri; Shefchek, Kent; Daugherty, Sean; Song, Yang; et al.
Abstract Helicobacter pylori, inhabitant of the gastric mucosa of over half of the world population, with decreasing prevalence in the U.S., has been associated with a variety of gastric pathologies. However, the majority of H. pylori‐infected individuals remain asymptomatic, and negative correlations between H. pylori and allergic diseases have been reported. Comprehensive genome characterization of H. pylori populations from different human host backgrounds including healthy individuals provides the exciting potential to generate new insights into the open question whether human health outcome is associated with specific H. pylori genotypes or dependent on other environmental factors. We report the genome sequences of 65 H. pylori isolates from individuals with gastric cancer, preneoplastic lesions, peptic ulcer disease, gastritis, and from asymptomatic adults. Isolates were collected from multiple locations in North America (USA and Canada) as well as from Columbia and Japan. The availability of these H. pylori genome sequences from individuals with distinct clinical presentations provides the research community with a resource for detailed investigations into genetic elements that correlate either positively or negatively with the epidemiology, human host adaptation, and gastric pathogenesis and will aid in the characterization of strains that may favor the development of specific pathology, including gastric cancer.